2008
DOI: 10.1111/1524-4725.2006.32002
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Surgical Scars with the Cryogen-Cooled 595 nm Pulsed Dye Laser Starting on the Day of Suture Removal

Abstract: The cryogen-cooled 595 nm pulsed dye laser is a safe and effective option to improve the cosmetic appearance of surgical scars in skin types I to IV starting on the day of suture removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 25 publications
(32 reference statements)
0
45
0
Order By: Relevance
“…Overall, these studies report improved subsequent scar appearance. 11,12 Only Hong et al 13 investigated the appropriate timing of laser intervention to reduce scarring. This study shows that the use of early fractional CO2 lasers 4 weeks after surgery or trauma is an effective and safe method to minimize scar formation, 13 substantiating the concept of "the earlier the treatment, the better."…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these studies report improved subsequent scar appearance. 11,12 Only Hong et al 13 investigated the appropriate timing of laser intervention to reduce scarring. This study shows that the use of early fractional CO2 lasers 4 weeks after surgery or trauma is an effective and safe method to minimize scar formation, 13 substantiating the concept of "the earlier the treatment, the better."…”
Section: Discussionmentioning
confidence: 99%
“…In previous publications, the most significant improvements were found in vascularity and pliability after therapy with the 585 nm or 595 nm PDL [1215]. …”
Section: Discussionmentioning
confidence: 99%
“…Nouri et al recently studied the use of the pulsed dye laser (PDL) at different wavelengths (585 nm and 595 nm) and with different pulse durations (short and long), and Conologue and Norwood demonstrated that the cryogen-cooled 595 nm PDL treatment is effective in improving the wound healing [1215]. …”
Section: Introductionmentioning
confidence: 99%
“…It was only later proposed for scar management with the rationale that increased vascularity is observed both clinically and histologically among hypertrophic scars [5][6][7]. Many pioneering studies on PDL therapy has been focused on incisional scars [8][9][10][11][12][13][14][15][16]. While the results have been generally positive, several centers have found less than enthusiastic results [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that PDL may have other effects that may better justify its use. Specifically, in a study of postsurgical incisions, Conologue et al showed no improvement in erythema with PDL therapy, but found significant improvements in both vascularity and pliability of surgical scars [11]. Others have found that pruritis, pain, texture and overall appearance were improved after treatments as described in Table 1b.…”
mentioning
confidence: 99%